Analysis of scored goals in the cerebral palsy football World Cup - Iván Peña-González,Juan F. Maggiolo,Alejandro Javaloyes &Manuel Moya-Ramón (Journal of Sports Sciences, 2022)
This study aimed to report the goal patterns in cerebral palsy (CP) football for a better understanding of the performance of this para-sport. All goals (270) of the 48 2019 IFCPF World Cup matches were analysed through match reports, and 65% of them were analysed by video footage. The results showed 5.6 goals per match. Teams that scored more and conceded fewer goals correlated to a better ranking position in the championship (r= 0.72-0.73; p< 0.01). The distribution of goals scored was not biased by halves (49.3% vs 50.7%; x^2= 0.1; p= 0.88) nor by 15-min periods (26.3% vs 23.0% vs 23.3% vs 27.4%; x^2= 0.5; p= 0.92). In 91.7% of the matches, the team which scored the first goal went on to win the match (x^2= 81.5; p< 0.01). FT3 players scored more goals by player (x^2= 22.1; p< 0.01), while there were no statistical differences in the distribution of goals conceded by goalkeepers according to their sport class (x^2= 4.7; p= 0.09). The goals were scored mainly from organized attacks (74.4%), from the penalty area (52.5%) and through individual action (51.9%). All this information could be crucial for coaches in CP football to plan their game strategies.